Perspektif Teologis Tentang Makna “Kehadiran” Dalam Kultur Digital - Romelus Blegur (Studia Philosophica et Theologica, 2022)
Digital culture is a new reality that affects human existence in the 21st century. With the development of technology, this culture also determines the way humans are present. Presence that could originally be interpreted through its personality is now eroded by a digital system that is completely artificial and meaningless. This causes a crisis of the meaning of presence and invites attention from various sides. Theologically, the meaning of presence cannot be represented by a technological system because technology is only a means without the intensity of awareness that is operationalized for the benefit of humans. Presence can only be interpreted through encounters between human beings in the wholeness of body, soul, and spirit which were originally created in the likeness and image of God. Therefore, in responding to digital culture, theology must be critical in order to address the meaning of presence so that it is not reduced or distorted by the negative impact of digital culture. This research uses a descriptive research method that aims to describe factual information, identify characteristics, trends, relationships and categories, as study material. The study materials used in this paper are sourced from relevant literature and support the completeness of research on the problems being studied, such as scientific journal articles and books.